Skill Gaps in the Workplace: Measurement, Determinants and Impacts - Seamus McGuinness; Luis Ortiz (Institute for the Study of Labor (IZA), 2015)
Optimal training decisions require employers to have accurate information about their workers' training needs. However, little is known with regard to the key factors determining the accurate transmission of worker training requirements. Using one of the few linked employer-employee surveys in the world, the 2006 Irish National Employment Survey, this paper identifies the key factors determining the correct identification of skill gaps within firms. The impact of skill gaps on average training expenditures and labour costs is also measured. The research finds that both HRM and collective bargaining arrangements are important factors in facilitating the accurate identification of skill gaps within firms. The analysis confirms that skill gaps are a key determinant of training expenditures and tend to raise average labour costs. Finally, the evidence suggests that employee perceptions of skill gaps may be prone to higher levels of subjective bias relative to those based on the employers' views.
Keywords: J20; J24; J50; 330; skill gaps; subjective bias; labour costs; training costs